Synaptotagmin-7 outperforms synaptotagmin-1 to promote the formation of large, stable fusion pores via robust membrane penetration - Kevin C. Courtney; Taraknath Mandal; Nikunj Mehta; Lanxi Wu; Yueqi Li; Debasis Das; Qiang Cui; Edwin R. Chapman (Nature Communications)
Abstract Synaptotagmin-1 and synaptotagmin-7 are two prominent calcium sensors that regulate exocytosis in neuronal and neuroendocrine cells. Upon binding calcium, both proteins partially penetrate lipid bilayers that bear anionic phospholipids, but the specific underlying mechanisms that enable them to trigger exocytosis remain controversial. Here, we examine the biophysical properties of these two synaptotagmin isoforms and compare their interactions with phospholipid membranes. We discover that synaptotagmin-1—membrane interactions are greatly influenced by membrane order; tight packing of phosphatidylserine inhibits binding due to impaired membrane penetration. In contrast, synaptotagmin-7 exhibits robust membrane binding and penetration activity regardless of phospholipid acyl chain structure. Thus, synaptotagmin-7 is a super-penetrator. We exploit these observations to specifically isolate and examine the role of membrane penetration in synaptotagmin function. Using nanodisc-black lipid membrane electrophysiology, we demonstrate that membrane penetration is a critical component that underlies how synaptotagmin proteins regulate reconstituted, exocytic fusion pores in response to calcium.